Oxidation behavior of SiCf/SiC composites prepared by melt infiltration process in water vapor corrosion environment - AI Yingjun; ZHAO Chunling; LANG Xudong; SHU Xiaowen; YANG Jinhua; LIU Hu; ZHOU Yiran; JIAO Jian (Cailiao gongcheng)
The oxidation behavior of SiCf/SiC composites， fabricated through the melt infiltration process， is meticulously investigated in a water vapor corrosion environment. The findings reveal that after exposure to water vapor corrosion at 800 ℃ and 1200 ℃ for 400 h， the flexural strength retention of uncoated samples is 78.8% and 74.9% respectively， whereas coated samples maintain flexural strengths of 95.9% and 93.0% respectively. The application of environmental barrier coatings effectively shield the material from direct contact with the corrosive water vapor medium， thereby mitigating the substantial decline in mechanical properties of the SiCf/SiC composites. Notably， the oxidation of the BN interfacial layer emerge as the primary factor contributing to the deterioration of the mechanical properties. Specifically， uncoated samples exhibit partial disappearance of the interfacial layer and the formation of holes between the fibers and the matrix after 400 h of corrosion at 1200 ℃， thereby compromising the protective role of the interface. Simultaneously， parts of the interface layer continue to bond the fiber and the matrix. The interplay between the oxidation of the BN interfacial layer and the SiC matrix is identified as the main cause for the decline in the mechanical properties of the SiCf/SiC composites.